Perception of the local community on the effects of fish mortality in lago do Rei in Careiro do Várzea – Amazonas (Research, Society and Development, 2023)
The whole world has been feeling the effect of climate change on people and nature. In the Amazon, extreme events have been more frequent, affecting populations that have their source of income from plant and animal extraction, such as the riverside populations, with the greatest impact. In order to understand which effects climate change has affected the events and nature of the Amazon, especially that related to the death of fish in lakes in the region, the present study was carried out listening to the perception of the main populations affected by this event, the riverside people and fishermen. of the communities around Lago do Rei. Twelve families were interviewed within the Lago do Rei area that is directly related to the lake, and semi-structured forms with open and closed questions were used. The perception of residents indicates that in the last 30 years the lake has been losing area, since many small lakes around Lago do Rei, which were rich in fish, today practically do not exist, especially during the dry season, there is a perception that the Lago do Rei has lost depth in recent years, which is believed to be due to grounding and the ease with which water enters the lake area during floods and extreme floods. The deposition of sediments at the bottom of the lake reduces the water profile during the dry season, increasing the temperature and causing greater activity of microorganisms and consuming oxygen, which would cause the death of fish in the lake as reported by residents from studies carried out previously by researchers who visited the site.